The violation of human rights in Iraq during the United States’ occupation: revisited - Jassam, Tariq Hussein; Ayub, Zainal Amin; Azmi, Ruzita (Medwell Journal, 2015)
This study provides a panoramic overview on the violation of Human Rights (HR) in Iraq during the United States’ (US) occupation from 2003-2012. It argues that these infringements including occupation-induced illegal mass expulsions to armed forces and police, human abuse, torture, rape, atrocities and deliberate murder in prisons, constitute heinous crimes against humanity.It demonstrates the ineffectiveness of all international principles involving HR to protecting Iraqi nationals despite the occupier being affiliated to the so called United Nations Security Council (UNSC).Furthermore, it is affirmed that these superpowers, being a member of UNSC, either modify the laws in the convention or misinterpret them to legally protect the officials involved in those criminal actions against HR.